PENGARUH KREDIBILITAS CELEBRITY ENDORSER TERHADAP MINAT BELI KONSUMEN - Jatmiko, Robby (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
The purpose of this study is to test whether the source credibility affectsbuying intention. The influence that endorser credibility dimensions (i.e.attractiveness, trustworthiness and expertise) have on purchase intentions of100 young consumers has been examined. The results showed that all of thethree credibility dimensions have a positive relationship with purchaseintention.